2018
DOI: 10.1021/acssuschemeng.8b01166
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Fluorescence Dual Signal Readout CuO-NiO/C Heterojunction Nanofibers-Based Nanoplatform for Imaging and Detection of Target Cancer Cells in Blood

Abstract: The development of multifunctional nanoplatform, which integrates biosensing and imaging diagnosis, for accurate identification of cancer cells in blood or other bodily fluids is critical for early cancer diagnosis and treatment. Herein, by using a facile single spinneret electrospinning technique followed by thermal treatment, CuO-NiO/C heterojunction nanofiber was synthesized. The resultant CuO-NiO/C nanofibers exhibited excellent catalytic activity toward ammonia borane (AB) hydrolysis, producing a marked p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…94 Similarly, Chang et al 95 found Fe 2 O 3 /BiOI electrospun hollow nanofibers to show high catalytic performance even under visible light for rhodamine B decomposition. Good catalytic properties and cycle stability was also recognized for PVA/ poly(acrylic acid)/Fe 3 O 4 /MXene@Ag nanoparticle composites, produced by electrospinning, 96 as well as CuO-NiO/carbon nanofibers which were carbonized after electrospinning 97 and Bi 2 MoO 6 /ZnFe 2 O 4 heterojunction nanofibers which were tested by rhodamine B degradation. 98 Electrospun magnetic nanofibers from a Fe 3 O 4 /PVA core and a poly(3-hydroxybutyrate) and PCL shell were decorated with TiO 2 nanoparticles by electrospraying, resulting in good photocatalytic activity under UV light.…”
Section: Removal and Decomposition Of Contaminantsmentioning
confidence: 88%
“…94 Similarly, Chang et al 95 found Fe 2 O 3 /BiOI electrospun hollow nanofibers to show high catalytic performance even under visible light for rhodamine B decomposition. Good catalytic properties and cycle stability was also recognized for PVA/ poly(acrylic acid)/Fe 3 O 4 /MXene@Ag nanoparticle composites, produced by electrospinning, 96 as well as CuO-NiO/carbon nanofibers which were carbonized after electrospinning 97 and Bi 2 MoO 6 /ZnFe 2 O 4 heterojunction nanofibers which were tested by rhodamine B degradation. 98 Electrospun magnetic nanofibers from a Fe 3 O 4 /PVA core and a poly(3-hydroxybutyrate) and PCL shell were decorated with TiO 2 nanoparticles by electrospraying, resulting in good photocatalytic activity under UV light.…”
Section: Removal and Decomposition Of Contaminantsmentioning
confidence: 88%
“…Benefiting from emerging nanomaterials, alternative approaches based on diverse conversion principles have been proposed, such as temperature, , distance, and color. , Among these parameters, air pressure as a classical physical element widely exists in bio/chemical reactions. , Yang’s group inventively exploited novel pressure-based bioassays using a handheld pressure meter. In these studies, a typical gas-generating reaction, that is, the decomposition of H 2 O 2 to O 2 , was chosen as the link between biomolecule recognition and signal readout. − Compared with other gas-generating reactions (e.g., hydrogen and carbon dioxide), this reaction is environment-friendly and has highly efficient liquid–gas phase conversion potency. Typically, platinum nanoparticles (PtNPs) have excellent peroxidase-like activity and can be utilized as the peroxidase mimics (nanozymes) to catalyze the reduction of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, a typical gas-generating reaction, that is, the decomposition of H 2 O 2 to O 2 , was chosen as the link between biomolecule recognition and signal readout. 17−20 Compared with other gas-generating reactions (e.g., hydrogen 21 and carbon dioxide 22 ), this reaction is environment-friendly and has highly efficient liquid−gas phase conversion potency. Typically, platinum nanoparticles (PtNPs) have excellent peroxidase-like activity and can be utilized as the peroxidase mimics (nanozymes) to catalyze the reduction of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Nanomaterials with pharmaceutical properties could be prepared by using many kinds of materials, including liposomes, polymers, biomacromolecules, and many other inorganic nanomaterials. [2,5,[11][12][13][14][15][16][17][18][19][20] In addition, the activity of these nanomaterials can be adjusted and improved by surface modification, [2,10,21] which will promote their in-depth study in biomedicine. The development of many advanced nanosystems in biomedicine have been inspired by these interesting properties.…”
Section: Introductionmentioning
confidence: 99%